Evaluasi Akurasi Moving Average dan Single Exponential Smoothing dalam Meramalkan Harga Jual Karkas Ayam Broiler dan Pakan Ayam Broiler (Studi Kasus: Jawa Timur) - Rijanto, Jonathan Billy; Zubair, Anis (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This study will use two forecasting methods: moving average and single exponential smoothing. Both use data from the past to predict what will happen in the future, therefore both techniques are referred to as time series methods. This method comparison was chosen to determine which method is most appropriate for predicting sales. This choice is based on the smallest error resulting from both methods which is known through the Mean Absolute Percentage Error (MAPE) calculation. Forecasting broiler chicken feed and carcasses can help farmers improve carcass quality, increase feed use, and increase profits. Forecasting can also make and find out whether there is a link between the price of broiler chickens and the price of broiler chicken feed.